Analisis Dampak Alokasi APBD dalam Perspektif Good Governance terhadap Pengembangan Infrastruktur Wisata Sejarah di Banten Lama - Anisa Ayu Aprianti; Laeli Nur Khalifah; Amealiea Prihatiningsih Malandy’s; Siti Nurlita (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The tourism sector is an important aspect in the sustainability of economic development in Indonesia. One of the tourism in Banten Province is Banten Lama Tourism, this area is an important historical site in Indonesia. As a manager, the Banten Provincial Government must revitalize the Banten Lama area including the physical restoration of buildings, infrastructure, and public facilities that have been damaged or degraded both in terms of function and aesthetics. The purpose of the research is to examine the extent to which the principles of good governance are applied in the process of APBD management in the revitalization of the Banten Lama area. This research uses a qualitative research type of case study approach a la Creswell. The existence of a revitalization budget report is a form of Banten Provincial Government has shown an initial form of accountability commitment in the management of public funds through the preparation and realization of the Banten Lama Area revitalization budget. The legal basis for revitalization is the 2016 Governor Regulation Number 14 article 5, Governor Decree Number 437/Kep.160-HUK/2018, the 2010 Cultural Heritage Law Number 11 in article 43 and the Momerandum of Understanding (MoU) Number 430/MOU.4-HUK/2017, 430/718-Setda/2017 & 516/MOU.24-HUK-2017 on October 4, 2017 by the Banten Provincial Government, Serang City Government and Serang Regency Government. The implication of the research is to understand how the impact on the development of Banten Lama tourism area.